If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -10x = 48 + -24x Solving 10 + -10x = 48 + -24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24x' to each side of the equation. 10 + -10x + 24x = 48 + -24x + 24x Combine like terms: -10x + 24x = 14x 10 + 14x = 48 + -24x + 24x Combine like terms: -24x + 24x = 0 10 + 14x = 48 + 0 10 + 14x = 48 Add '-10' to each side of the equation. 10 + -10 + 14x = 48 + -10 Combine like terms: 10 + -10 = 0 0 + 14x = 48 + -10 14x = 48 + -10 Combine like terms: 48 + -10 = 38 14x = 38 Divide each side by '14'. x = 2.714285714 Simplifying x = 2.714285714
| 8x-10=78 | | 6x+18=14x+78 | | 4x^2-19x+24=4x+9 | | 6x^2+41x-7=0 | | X^2+11X-8=8X+2 | | 3*102X-6=24 | | n^5=2 | | 4x^2-33x-49=-4x+4 | | n+21=46 | | n*2=42 | | n+34=46 | | n-11=16 | | n-9=5 | | n*2=14 | | n+7=11 | | 6n+4=22 | | 3x=13x-80 | | (n+4)*8=40 | | n+4*8=40 | | (n-8)*4=20 | | 3x=13x-82 | | 5*n=24 | | 3ln(6x)=6 | | n*5=65 | | x^4+2=29 | | -11(t-3)-(t+7)=9 | | 5*4x=35 | | n+5=45 | | n+33=44 | | n+7=17 | | (n+2)*8=32 | | (n-3)*5=30 |